Towards the Future Internet A European Research Perspective - Tselentis, Georgios (IOS Press, 2013)
The Internet is a remarkable catalyst for creativity, collaboration and innovation providing us today with amazing possibilities that just two decades ago it would have been impossible to imagine; and yet we are not amazed! It is only 20 years ago that Tim Berners-Lee invented the Web and two years later, CERN publicized the new World Wide Web project. If one could take a trip back in time with a time machine and say to people that today even a child can access for free a satellite image of any place on earth, interact with other people from anywhere and query trillions of data all over the globe with a simple click on his/her computer they would have said that this is science fiction!